Some data on food of gaur Bos gaurus H. Smith, 1927 (Artiodactyla: Bovidae) in Vietnam - Ha, Nguyen Manh; Nghia, Tran Dinh (Academia Journal of Biology, 2014)
Study on food of Gaur (Bos gaurus H. Smith, 1927) was undertaken within 2004 to 2006 in most of Gaur distribution areas in Vietnam. Total of 234 plant specimens were collected for species identification. Total of 125 species that belong to 42 plant families which Gaur uses for food was identified. Leaves and buds are among the most favor portions of plant that used by Gaur. In addition, the plants were recorded in a variety of habitats that shows the wide range of browsing area of Gaur. The food for Gaur in captivity is almost entirely different from those in the wild. However, Gaur shows very well adapt in both conditions. The highly adaptation of food would explain for wide range of the Gaur in this area. This important information on food of Gaur would provide vital help on Gaur conservation management. Of that, any future plan on Gaur habitat management should refer to an appropriate percentage of browsing area and variety of habitat types within Gaur conservation area. In addition, information on food of Gaur would help any future ex-situ conservation or help zoo to provide sufficient food for Gaur in captivity. Any further research on food and ecology of Gaur should be highly encouraged in order to provide complete information on this species that will help conservation of Gaur and other endangered species in the future.